Teaching a second foreign language in Portuguese-Spanish translator training: An analysis of the study plans in two Peruvian universities - Meléndez-Robles, Oscar Xavier (2024)
The study of foreign language training for translators/interpreters has gained relevance in Translation Studies. This fact can be seen in the various studies that address the importance of having specific training aimed at teaching and learning the language as a translator’s tool, which is related to the translation process, and the development of translation competence (Oster, 2008; Gomes, 2017). In the case of undergraduate programs in translation and interpreting in Lima (Peru), the two universities selected for this study offer Portuguese as C Language, whose learning should aim to develop more specific skills (Hurtado Albir, 1999), through material designed for this purpose (Cerezo, 2020). This article aims to present a comparative analysis of the curricular structures of the programs of the two chosen universities and the bibliography contained in the study plans of the Portuguese language subjects to present a bibliographic portrait of the material used, based on documentary analysis (Scott, 2006; Gil, 2008), supported by the qualitative approach and a starting point for more deep future research on translator training in Portuguese/Spanish. In the analysis, we were able to identify similarities and differences regarding the material used in the afore mentioned subjects in these higher education institutions and that it mainly aims to develop communicative competence in the foreign language.